Medication therapy: adherence, knowledge and difficulties of elderly people from bipolar disorder Terapéutica medicamentosa: adhesión, conocimiento y dificultades de personas ancianas portadoras de trastorno bipolar Terapêutica medicamentosa: adesão, conhecimento e dificuldades de idosos com transtorno bipolar - Ligiane Paula da Cruz; Patrícia Monforte Miranda; Kelly Graziani Giacchero Vedana; Adriana Inocenti Miasso (Universidade de São Paulo, 2011)
This study aimed to verify the adherence, knowledge and the difficulties of elderly patients with Bipolar Affective Disorder (BAD) in relation to the prescribed pharmacological therapy for the control of this disorder. The study included 17 elderly patients with BAD treated at a Mental Health Center. Semi-structured interviews were conducted and scales were applied. The data were analyzed using a quali-quantitative approach. A low level of adherence to the pharmacological treatment and a deficit in knowledge in relation to the medication were identified, especially regarding the dose and frequency of administration. Among the difficulties inherent to the pharmacotherapy, the obligation of polypharmacotherapy, the desire to quit the pharmacological treatment, limitations in the self-administration of the medication, collateral effects, and doubts about the need for the medication were related. Investment is needed in educational activities and in the promotion of adherence that address the difficulties experienced by elderly people with BAD in the following of the pharmacotherapy in order to ensure safety in the medication therapy. Este estudio tuvo como objetivo verificar la adhesión, el conocimiento y las dificultades de ancianos con Trastorno Afectivo Bipolar (TAB) en relación a la terapéutica medicamentosa prescrita para control del referido trastorno. Participaron del estudio 17 ancianos con TAB atendidos en un Núcleo de Salud Mental. Fueron realizadas entrevistas semiestructuradas y aplicación de escalas. Los datos fueron analizados con abordaje cualitativo-cuantitativo. Se identificó bajo grado de adhesión al tratamiento farmacológico y déficit en el conocimiento sobre los medicamentos, especialmente sobre las dosis y frecuencia de administración. Entre las dificultades inherentes a la fármacoterapia fueron relatadas la obligatoriedad de la polifármacoterapia, el deseo de terminar el tratamiento farmacológico, las limitaciones en la auto-administración de los fármacos, los efectos colaterales y las dudas sobre la necesidad de los medicamentos. Se concluye que son necesarias inversiones en acciones educativas y de promoción de la adhesión que contemplen las dificultades experimentadas por los ancianos con TAB en el seguimiento de la fármacoterapia para garantizar la seguridad en la terapéutica medicamentosa. Este estudo teve como objetivo verificar a adesão, o conhecimento e as dificuldades de idosos com transtorno afetivo bipolar (TAB), em relação à terapêutica medicamentosa, prescrita para controle do referido transtorno. Participaram do estudo 17 idosos com TAB atendidos em um núcleo de saúde mental. Foram realizadas entrevista semiestruturada e aplicação de escalas. Os dados foram analisados com abordagem quali-quantitativa. Identificou-se baixo grau de adesão ao tratamento farmacológico e déficit no conhecimento sobre os medicamentos, especialmente sobre as doses e frequência de administração. Entre as dificuldades inerentes à farmacoterapia relataram-se: a obrigatoriedade da polifarmacoterapia, o desejo de encerrar o tratamento farmacológico, limitações na autoadministração dos fármacos, efeitos colaterais e dúvidas sobre a necessidade dos medicamentos. São necessários investimentos em ações educativas e de promoção da adesão que contemplem as dificuldades vivenciadas pelos idosos com TAB, no seguimento da farmacoterapia, para garantia de segurança na terapêutica medicamentosa.